Britten's Gloriana David McVicar (stage director), Ivor Bolton (conductor) -- With Anna Caterina Antonacci (Queen Elizabeth I), Leonardo Capalbo (Robert Devereux, Earl of Essex), Paula Murrihy (Frances, Countess of Essex) ... - Britten, Benjamin 1913-1976 (Wahoo Production - Teatro Real, 2018)
First performed in June 1953 to mark the coronation of Queen Elizabeth II, Benjamin Britten's Gloriana painted a nuanced and complex portrait of the new queen's predecessor in name. In her repeated clashes with the Earl of Essex--a longtime favorite of the queen who was ultimately put to death for treason--Elizabeth I is depicted as flawed and vain, human and sympathetic. To the public in 1953, eager to embrace a robust postwar optimism and celebrate their young monarch, the tragic and morally complicated subject matter of Britten's opera was unpalatable. Its chilly reception kept the work out of opera houses for years, but a recent critical reappraisal has given audiences sublime new stagings like this one, starring the superb Anna Caterina Antonacci in the lead role. "One of the finest artists of her generation" (OperaWire), Antonacci's elastic, emotive voice brings high drama to the Elizabethan tragedy, supported admirably by a top-notch cast, including Leonardo Capalbo as Essex. The reliably outstanding Ivor Bolton conducts the Orchestra of the Teatro Real de Madrid in this "landmark" production, the "vindication of a neglected masterpiece" (Bachtrack)
Keywords: Operas; opera; Filmed performances; Internet videos